Comercio y mercaderes en el Valle del Duero : siglos XV y XVI - Hilario Casado Alonso (Estudios de Historia de España, 2016)
This article analyses the evolution of trade in the Duero valley during the XV and XVIth centuries. After explaining how commercial and financial activities were highly developed at that time, the paper studies the general characteristics of the economy, the factors of trade growth, the networks of internal trade and fairs, as well as foreign trade with Europe and America.